Catheter based intracoronary brachytherapy leads to increased platelet activation. Issue 2 (16th January 2004) - Jaster, M; Fuster, V; Rosenthal, P; Pauschinger, M; Tran, Q-V; Janssen, D; Hinkelbein, W; Schwimmbeck, P; Schultheiss, H-P; Rauch, U
Abstract : Background: Vascular brachytherapy (VBT) after percutaneous coronary intervention (PCI) is associated with a higher risk of stent thrombosis than conventional treatment. Objective: To investigate in vivo periprocedural platelet activation with and without VBT, and to assess a possible direct effect of radiation on platelet activation. Design: Of 50 patients with stable angina, 23 received VBT after PCI, while 27 had PCI only. The 23 patients who received VBT after PCI were pretreated for one month with aspirin and clopidogrel. Platelet activation was assessed by flow cytometry. Results: The two patient groups did not differ in their platelet activation before the intervention. There was a significant increase in activation immediately after VBT, with 21.2% (interquartile range 13.0% to 37.6%) thrombospondin positive and 54.0% (42.3% to 63.6%) CD 63 positive platelets compared with 12.7% (9.8% to 14.9%) thrombospondin positive and 37.9% (33.2% to 45.2%) CD 63 positive platelets before the intervention (p < 0.001 and p < 0.01, respectively). Patients without VBT had no periprocedural difference in platelet activation immediately after PCI. No increase in platelet activation was found after ex vivo irradiation of blood samples obtained from healthy controls. Conclusions: Catheter based intracoronary VBT carried out according to current standards is highly thrombogenic. The current antithrombotic treatment with aspirin and clopidogrel is not sufficient to suppress platelet activation during the procedure. From in vitro experiments, it appears that platelet activation during brachytherapy is not caused by irradiation but by the procedure of catheter based VBT.